The Preliminary Study for Effect of Plant Extract on Concentration of Heavy Metals in Soil. Issue 1 (December 2021) - Lee, Li Na; Guo, Xinxin; Lim, Jinq Shiou; Wong, Rou Hui; Ng, Choon Aun; Bashir, Mohammed JK; Lee, Lim Fang
Abstract: Heavy metal contamination in soils had arisen into a more prominent problem as a result of increasing anthropogenic activities like manufacturing, mining, excessive application of agricultural chemicals and inappropriate disposal of wastes. Researchers across the globe had been striving to discover and develop methods to restore the soil back to its original condition with an assortment of remediation techniques that varies from treatment mechanism for various soil and contamination condition. Majority of the existing techniques have drawbacks like high energy consumption, specificity on the site condition, limitations on applicable contaminants, side effects after treatment, and also being uneconomical. More and more researchers are beginning to divert their attention into using organic stabilizers for treatment of soil heavy metal contamination in recent years after learning about its potential after numerous research showed promising reduction on the bioavailability and mobility of heavy metals. Due the lack of study on liquid-form organic stabilizers, the authors dedicated this research into implementing plant extract (TM) in the immobilization of heavy metals in soil. For comparison purpose, sodium alginate (SA), a proven organic stabilizer had been incorporated into the experiment to evaluate the performance of plant extract to immobilize cadmium (Cd), chromium (Cr), and manganese (Mn) from the metal-spiked soil samples in this research. The study findings suggested that the SA increased the unstable fractions, namely the exchangeable and carbonate fractions, of Cd relative to the untreated soil sample by 10.3 % to 5.2. On the other hand, the TM yields a result of 0.1 % to 1.1 % reduction of the unstable Cd. For the unstable Cr, both SA and TM decreased the concentration levels in the soil by 2.5 % to 8.0 % and 6.1 % to 7.9 % respectively. The results for Mn showed that the SA is able to decrease the concentration of its unstable fractions by 2.0 % to 7.5 % while the TM increases the concentration by 11.7 % to 1.5 %. In general, lower concentration of heavy metals in the unstable fractions was detected as the dosage of soil stabilizers applied increases. The application of soil stabilizers at 10 % weight percentage yields the lowest reading of unstable heavy metals in comparison with samples with lower dosage.